Tailoring an economic-ecological-tourism coupling framework for arid-region ski resorts: A PSR model-based case study of Xinjiang, China - Bin Jiang; Chunxiang Zhang; Zhennan Liu; Jiedong Wen; JiuLian Zhu; Liping Xu; FeiTeng Wang (Ecological Indicators, 2025)
Arid regions constitute 40.6 % of the global landmass, with their climatic characteristics of low precipitation, high evaporation, and ecological fragility imposing severe challenges on ice-snow tourism development. Take the Sierra Nevada in Spain and Utah in the United States as examples, large-scale development of ski resorts in arid areas has triggered ecological crises such as water resource depletion and vegetation disturbance. However, existing studies suffer from insufficient understanding of the unique interaction mechanism of “rigid water resource constraints-tourism development-ecological response” in arid regions, leading to a shortage of precise assessment tools. To bridge this gap, this study takes 31 S-class ski resorts in Xinjiang, China (with 2011–2023 panel data) as a case, constructs an “Economic-Ecological-Tourism” (EET) coupling coordination indicator system based on the PSR model, and integrates entropy-weighted TOPSIS, obstacle degree model, and grey prediction model to form a closed-loop methodology of “indicator screening-obstacle diagnosis-trend prediction”. The findings show that the EET coupling coordination degree of Xinjiang ski resorts has increased from near-disharmony (0.386) to primary coordination (0.636), with the type shifting from “economy-lagging” to “tourism-lagging”. Tourism traffic convenience (road density, passenger turnover) emerges as the core obstacle factor. The coupling coordination degree is projected to continue rising in the next decade, stabilizing in the primary coordination stage (D ≥ 0.65) by 2027. This study validates the “asymmetric response” theory of ecological thresholds in arid regions, and proposes policy recommendations such as the “ecological rigid constraint coefficient” and “inclusion of carbon emissions in environmental certification”, providing a transplantable quantitative management paradigm for ski resorts in arid regions of Central Asia and North America.